Modeling of collapsing cavitation bubble near solid wall by 3D pseudopotential multi-relaxation-time lattice Boltzmann method. (February 2018) - Shan, Minglei; Yang, Yu; Peng, Hao; Han, Qingbang; Zhu, Changping
Understanding the dynamic characteristic of the cavitation bubble near a solid wall is a fundamental issue for the bubble collapse application and prevention. In the present work, an improved three-dimensional multi-relaxation-time pseudopotential lattice Boltzmann model is adopted to investigate the cavitation bubble collapse near the solid wall. With respect to thermodynamic consistency, Laplace law verification, the three-dimensional pseudopotential multi-relaxation-time lattice Boltzmann model is investigated. By the theoretical analysis, it is proved that the model can be regarded as a solver of the Rayleigh–Plesset equation, and confirmed by comparing the results of the lattice Boltzmann simulation and the Rayleigh–Plesset equation calculation for the case of cavitation bubble collapse in the infinite medium field. The bubble collapse near the solid wall is modeled using the improved pseudopotential multi-relaxation-time lattice Boltzmann model. We find the lattice Boltzmann simulation and the experimental results have the same dynamic process by comparing the bubble profiles evolution. Form the pressure field and the velocity field evolution it is found that the tapered higher pressure region formed near the top of the bubble is a crucial driving force inducing the bubble collapse. This exploratory research demonstrates that the lattice Boltzmann method is an alternative tool for the study of the interaction between collapsing cavitation bubble and matter.